STRUKTUR EKONOMI DAN SEKTOR UNGGULAN SEKTORAL PADA PROPINSI RIAU - Rahmatullah Rahmatullah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2012)
This study aims to examine and analyze the structure of the economy, the dominant sector of economic regions, economic sectors effect on the growth of regional economy and the impact on the growth of leading sectors of economic sectors in the province of Riau. The research shows that The economic structure based on the demand and supply of output, gross value added and employment. Riau is the main structure: The food and beverage industry, tobacco, trade, construction, other services and goods paper & printing industry. Dominant sector in 2000 Riau oil, gas and geothermal energy, petroleum refining, transportation equipment industry, machinery & equipment, trade, plantation crops and buildings. Year 2005 plantation crops, food industry, beverages & tobacco, paper and printed material industry, commerce, fisheries, mining, oil, gas and geothermal energy, and buildings. The variable government investment, suwasta investment, exports, imports, employment, forward linkage, backward lingkage, the impact of output and gross value added impact of simultaneous positive effect on regional economic growth (GDP) in Riau.DOI: 10.15408/sjie.v1i1.2596